2007
DOI: 10.1007/s10265-007-0097-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biodiversity in the moss Leptodon smithii (Neckeraceae) in relation to habitat disturbance and fragmentation

Abstract: Bryophytes seem particularly suitable to investigate genetic diversity in relation to habitat disturbance due to their large employment as bioindicators and to the recent application of molecular markers to moss population studies. Genetic variation and structure were analysed in seven urban, extraurban and remote populations of Leptodon smithii, an epiphytic moss of Quercus ilex, a phanerogamic species of Mediterranean climax vegetation. A total of 210 individual shoots were DNA extracted and amplified with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 50 publications
1
15
0
1
Order By: Relevance
“…The authors found that the detected genetic variability is higher in extraurban than in urban sites and the level of genetic variation depends on population size -large populations had a higher level of polymorphism than small ones. Moreover, they found that undisturbed sites maintain a high level of intraspecific variation and ancient biodiversity, even if populations are small (Spagnuolo et al, 2007). Similar results, inferred from microsatellite markers, were reported by Wilson & Provan (2003) for the moss Polytrichum commune Hedw.…”
Section: Genetic Variation and Habitat Disturbancesupporting
confidence: 63%
See 1 more Smart Citation
“…The authors found that the detected genetic variability is higher in extraurban than in urban sites and the level of genetic variation depends on population size -large populations had a higher level of polymorphism than small ones. Moreover, they found that undisturbed sites maintain a high level of intraspecific variation and ancient biodiversity, even if populations are small (Spagnuolo et al, 2007). Similar results, inferred from microsatellite markers, were reported by Wilson & Provan (2003) for the moss Polytrichum commune Hedw.…”
Section: Genetic Variation and Habitat Disturbancesupporting
confidence: 63%
“…Similarly, a deleterious effect of habitat disturbance on the level of genetic diversity was observed in the moss Leptodon smithii (Hedw.) Weber & Mohr (Spagnuolo et al, 2007). The authors found that the detected genetic variability is higher in extraurban than in urban sites and the level of genetic variation depends on population size -large populations had a higher level of polymorphism than small ones.…”
Section: Genetic Variation and Habitat Disturbancementioning
confidence: 96%
“…Narasimhan et al 2006;Padmesh et al 2006;Joshi & Dhawan 2007, Refoufi & Esnalut 2008Yao et al 2008;Cordeiro et al 2008;Choudhury et al 2008;), but there is very few studies on cryptogams incl. bryophytes (e. g. van der Velde & Bijlsma 2003;Werner & Guerra 2004;Sabovljević et al 2005Sabovljević et al , 2006Spagnuolo et al 2007Spagnuolo et al , 2008Grundmann et al 2008, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…ISSR amplifications of single ramets were performed following Spagnuolo et al (2007b). The primers used for ISSR analysis are listed in Table 2.…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%